ISSUES OF HIGHER EDUCATION (ARTICLE-BOOK REVIEW «HISTORY OF HIGHER SCHOOL IN SVERDLOVSK REGION» BY S. S. NABOJCHENKO) - Evgeny M. Dorozhkin; Nikolaj K. Chapaev (Образование и наука)
The aim of the given article is to consider a number of actual issues of development of the Russian higher school and vocational training, through the material presented in the book «History of higher school in Sverdlovsk region» by S. S. Nabojchenko. 1. Respect for historical-pedagogical experience at realisation of principal reforms in education is essential. The cumulative consideration both positive, and the negative facts and results of vocational training allows to project an appropriate planning chart of educational reforms and to avoid frequency of missteps of the past. 2. The analysis of activity of Councils of rectors of high schools shows that the given association carries out the important mission on creation of edifice system of socially-government higher education as on regional and federal levels. 3. Reflecting on «a brain drain» problem, authors fairly specify in current contradiction: on the one hand, Russian employers are not satisfied with graduates of the Russian high schools, at another point – many of them, going abroad, quite successfully cope there with the professional duties with a degree in their field. This fact raises some questions about the common statement about bad quality of preparation in our high schools. The problem of quality of preparation of experts is supplemented with a problem of quality of working conditions. 4. An application training Master’s degree program is offered by the authors of the presented article as one of the possible means of the problem solution of professional formation of the person at a postgraduate stage.